Immune cells and RBCs derived from human induced pluripotent stem cells: method, progress, prospective challenges - Jiang, Jin-he; Ren, Ru-tong; Cheng, Yan-jie; Li, Xin-xin; Zhang, Gui-rong (Frontiers in Cell and Developmental Biology, 2024)
Blood has an important role in the healthcare system, particularly in blood transfusions and immunotherapy. However, the occurrence of outbreaks of infectious diseases worldwide and seasonal fluctuations, blood shortages are becoming a major challenge. Moreover, the narrow specificity of immune cells hinders the widespread application of immune cell therapy. To address this issue, researchers are actively developing strategies for differentiating induced pluripotent stem cells (iPSCs) into blood cells in vitro. The establishment of iPSCs from terminally differentiated cells such as fibroblasts and blood cells is a straightforward process. However, there is need for further refinement of the protocols for differentiating iPSCs into immune cells and red blood cells to ensure their clinical applicability. This review aims to provide a comprehensive overview of the strategies and challenges facing the generation of iPSC-derived immune cells and red blood cells.